The Camera-Dancer: A Dyadic Approach to Improvisation - Nikolai, Jennifer R A (The International Journal of Screendance, 2016)
How can the light-weight video camera in the hands of the improvising dancer, enhance compositional choices in moment-to-moment or retrospective decision-making in studio? I propose that the camera in the hands of the dancer moving and passing the camera between dancing subjects/objects is a form of improvisational investigation. I refer to this dyadic approach as camera-dancer, distinct from the tradition of the camera as archival instrument, in multimedia or interactive performance. The camera-dancer as instigator/provocateur opens perspectives towards composition otherwise not considered. In this paper I highlight approaches that moving image pioneers Maya Deren and Dziga Vertov held towards the camera and how this has informed studio improvisations myself and dance collaborators apply. Perhaps it is how we as dancing operators react to moments before, discoveries in the moment, a retrospective ‘camera consciousness,’ that enhances compositional openings as a form of camera dramaturgy.